2020
DOI: 10.1109/access.2019.2961694
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Synthesis and Dielectric Properties of c-C4F8O With Its CO2/N2 Mixtures as SF6 Alternatives in Gas-Insulated Applications

Abstract: The usage and emission of SF 6 has been regulated because of high Global Warming Potential (GWP) and long atmospheric lifetime as an insulator in high voltage power transmission equipment. This paper proposes cC 4 F 8 O and its mixtures as a substitute for SF 6 with low GWP and superior insulation performance. cC 4 F 8 O is synthesized by 1,4-diiodoperfluorobutane and fuming sulfuric acid with the yield of 55.7% under optimal conditions. The GWP of cC 4 F 8 O is about one-third that of SF 6 and its dielectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…We observed the sensitivity of Q ION with the IP and found linear relation for Q ION (peak) with N in absence of much deviation in IP for these targets (figure 17). We also correlated the Q ION (peak) with IP and polarizability (figures [18][19] and observe the linear relation as predicted by Bart et al [48]. Using these correlation analyses we predicted the dipole polarizability for C x F 2x O (x = 2, 5, 6) and found that our predicted polarizabilities are in excellent agreement with those computed using online software www.chemspider.com.…”
Section: Discussionsupporting
confidence: 73%
“…We observed the sensitivity of Q ION with the IP and found linear relation for Q ION (peak) with N in absence of much deviation in IP for these targets (figure 17). We also correlated the Q ION (peak) with IP and polarizability (figures [18][19] and observe the linear relation as predicted by Bart et al [48]. Using these correlation analyses we predicted the dipole polarizability for C x F 2x O (x = 2, 5, 6) and found that our predicted polarizabilities are in excellent agreement with those computed using online software www.chemspider.com.…”
Section: Discussionsupporting
confidence: 73%
“…Figure 3 shows the device of power frequency breakdown. The effectiveness of the breakdown device has been verified in references [20,21]. The cavity mainly includes a stainless-steel base, silica glass, gas filling valve and electrode spacing adjustment screw.…”
Section: Power Frequency Breakdown Test Platformmentioning
confidence: 99%
“…Luo's group is committed to the development of the insulating gas [19][20][21][22]. In our recent study, the trans-1,1,1,4,4,4hexafluoro-2-butene (HFO-1336mzz(E), CF 3 -CH=CH-CF 3 ) is proposed as a potential insulating medium.…”
Section: Introductionmentioning
confidence: 99%
“…The quest for substitute gases represents a crucial stride toward realizing a sustainable energy prospect. Substituting SF6 with alternative gases can reduce the ecological footprint of highvoltage applications and positively contribute to climate change amelioration [14,15]. Conventional gases such as dry air, nitrogen, carbon dioxide, or mixtures exhibit a lower global warming potential than SF6, but their dielectric strength is limited to only 40% or less [16].…”
Section: Introductionmentioning
confidence: 99%